Can combination of Day 3 and Day 5 embryo morphology be useful to predict pregnancy in in-vitro fertilization cycles? - Demir, A.; Kose, M.; Bozdag, G.; Sokmensuer, L. Karakoc; Sever, A.; Gunalp, S. (I R O G Canada, Inc, 2014)
Objective: To determine whether embryos having all top qualified both on Day 3 and Day 5 have higher pregnancy rates than the others. Materials and Methods: The study included 143 consecutive cycles were recruited in which Day 5 embryo transfer was available. Cleavage stage embryos were graded according to 1 to 4 scoring system, based on fragmentation, cell symmetry, and blastomere number. Among cleavage stage embryos, Grade 1 and Grade 2a/2b were further stratified as 'top quality' embryos to be transferred, others were defined as control group. Blastocyst stage embryos were graded from 1 to 6 according to intracellular mass (ICM) and trophectoderm (TB). Day 5 fresh embryo transfer was performed in all cases using soft catheter. Positive pregnancy test was accepted when serum beta-human chorionic gonadotrophin (beta-hCG) exceeded 20 mIU/ml. Results: On the cleavage stage, top quality embryo was available in 47 of 143(32.9%) cases. Of the 47 embryos, the number of cases reaching any Grade 4, 3 quality, and early blastocyst on Day 5 were 22 (46.8%), 15 (31.9%), and 10 (21.3%). The respective figures on the control group (n=96) were 33 (34.4%), 37 (38.5%), and 26 (27.1%) (p > 0.05). The pregnancy rates were also similar. Conclusion: All top qualified embryos both on Day 3 and 5 did not reveal higher pregnancy rate than the others.
Keywords: Embryo morphology; Blastocyst; In vitro fertilization